The ZW10 and Rough Deal checkpoint proteins function together in a large, evolutionarily conserved complex targeted to the kinetochore. - Scaerou, F.; Starr, D.A.; Piano, F.; Papoulas, O.; Karess, R.E.; Goldberg, M.L. (Journal of Cell Science, 2001)
The zeste-white 10 (zw10) and rough deal (rod) genes of Drosophila both encode kinetochore components, and mutations in either gene greatly increase the missegregation of sister chromatids during mitosis. Here, we present genetic, cytological and biochemical evidence for a close, evolutionarily conserved relationship between the ROD and ZW10 proteins. We show that the phenotypes caused by disruption of either gene's function are similar in Drosophila and in C. elegans. No additive effects are observed in zw10; rod double null mutants. In flies, the two proteins always colocalize and, moreover, require each other for their recruitment to the mitotic apparatus. The human ROD and ZW10 homologs also colocalize on HeLa cell kinetochores or kinetochore microtubules throughout most but not all of mitosis. Finally, we show that in both Drosophila and human cells, ROD and ZW10 are in fact physically associated, and in Drosophila these proteins are together constituents of a large (700-900 kDa), soluble macromolecular complex.